2021
DOI: 10.1016/j.jbc.2021.100792
|View full text |Cite
|
Sign up to set email alerts
|

Real-time identification of two substrate-binding intermediates for the light-driven sodium pump rhodopsin

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…The time-resolved spectra showed an ~10-nm blueshift from T = 0 to 1 s, and it then slightly redshifted afterward. Previously, we carried out the nanosecond flash photolysis of IaNaR at room temperature (7) and observed the redshifted intermediates in the millisecond region as shown in Figure 2B. The detailed kinetic analysis revealed that the millisecond process includes the four redshifted intermediates referred to as O1, O2, N, and NaR' (Figure 1C).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The time-resolved spectra showed an ~10-nm blueshift from T = 0 to 1 s, and it then slightly redshifted afterward. Previously, we carried out the nanosecond flash photolysis of IaNaR at room temperature (7) and observed the redshifted intermediates in the millisecond region as shown in Figure 2B. The detailed kinetic analysis revealed that the millisecond process includes the four redshifted intermediates referred to as O1, O2, N, and NaR' (Figure 1C).…”
Section: Resultsmentioning
confidence: 88%
“…The sample was sealed with an O ring and another glass plate, and set in the liquid-nitrogen cooled cryostat (Optstat DN2; Oxford Instruments) for the spectroscopic measurements. mM NaCl) measured in our previous nanosecond flash photolysis study (7) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations